Empowering indigenous communities for sustainable local tourism in Sungai Bumbun - Mohd Razali, Ahmad Aliff Ismail; Azan, Zaliza; Abu Seman, Shahri (Jurnal Evolusi, 2024)
This research investigates various approaches aimed at enhancing the capability of the Orang Asli community residing in Sungai Bumbun to engage in and derive advantages from the sustainable development of local tourism. The primary focus of this study pertains to the potential adverse effects of tourism on indigenous cultures and habitats. This study aims to investigate the design of local tourism programmes that can effectively empower the Orang Asli community, while also safeguarding its cultural legacy and natural resources. A qualitative methodology was utilised to conduct in-depth interviews with key stakeholders engaged in community empowerment and local tourist initiatives. The significance of collaboration among the Orang Asli community, government entities, and non-governmental organisations (NGOs) was unveiled through data analysis. Education has become a crucial element, providing the community with the necessary skills and information to efficiently handle tourism. The results underscore the importance of incorporating cultural preservation into tourism endeavours and advocating for sustainable methods in order to mitigate environmental consequences. The findings of this study hold substantial significance for the advancement of sustainable tourism in indigenous communities. Local tourism in Sungai Bumbun can enhance the economic and social welfare of the Orang Asli people by promoting cooperation, empowering communities via education, and giving priority to cultural and environmental sustainability. This approach also ensures the protection of their distinct identity and environment.